Reduction of Menstrual Pain (Dysmenorrhoea) with Lemongrass Aromatherapy Efleruage Massage Technique in Women of Fertile Age - Marwang, Sumarni; Passe, Rosita (Jurnal Midwifery, 2025)
Introduction Reproductive health problems in women are a complex problem. Common factors that cause reproductive health problems are the poor health status of Indonesian women, changes in sexual behavior (marrying young and having sex outside of marriage), poor nutrition, diseases that can affect reproductive health and poor environmental sanitation. One reproductive health problems caused by an environment with poor sanitation, namely vaginal discharge. Vaginal discharge is a discharge from the vagina other than menstrual blood. Vaginal discharge that is too long and left can cause complications. Complications can occur because bacteria in the vagina can enter the uterine cavity then into the fallopian tubes and up to the ovaries and finally into the pelvic cavity. Method The type of research used is experimental research with a Posttest-Only Control Design approach where there are two groups, each selected randomly (R). Each group or sample, namely women of childbearing age who experienced vaginal discharge, were given treatment, but the treatment given was different. Group 1 was given water boiled with betel leaves and group 2 was given water boiled with turmeric. Result Based on statistical tests with a value of P: 1,000 > α: 0.05, Ho is accepted so it can be concluded that there is no difference in giving betel leaves and turmeric in treating vaginal discharge, in this case both betel leaves and turmeric can treat vaginal discharge. Conclusion It can be concluded that there is no difference in giving betel leaves and turmeric in treating vaginal discharge, in this case both betel leaves and turmeric can treat vaginal discharge